Description Of Knowledge About Caries Using Flash Card Media Among Fourth Grade Students at SDN Nawangan 1, Pacitan Regency - Nurjanah, Arum; Hidayati, Sri; Isnanto (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Dental and oral health disorders, particularly dental caries, are prevalent among primary schoolaged children. Preliminary results from SDN Nawangan 1 indicated that 14 of 15 pupils (93.3%) had dental caries. This research intends to describe the degree of awareness about dental caries among fourth-grade students at SDN Nawangan 1, Pacitan Regency, using flash card media. This research employed a descriptive approach involving 30 student respondents. Data collection instruments based on surveys. With an average score of 91.7%, students demonstrated strong understanding of the definition, causes, consequences, prevention, and treatment of dental caries. Flash card media were used as a visual and engaging tool to deliver information effectively. The findings of this study suggest that educational media such as flash cards play a supportive role in conveying dental health information to elementary school students.